Effects of high progesterone on outcomes of in vitro fertilization-embryo transfer in patients with different ovarian responses. (June 2015) - Li, Peng-fen; Zhu, Hong; Tan, Li; Zhao, Dong-mei; Ma, Li-ying; Xiang, Yun-gai; Zhang, Dan; Dou, Qian; Lu, Na
Abstract The data of 3, 841 cycles undergoing in vitro fertilization-embryo transfer (IVF-ET) in our reproductive Center between January 2003 and December 2013 were retrospectively analyzed. According to the number of oocytes retrieved, this study was divided into the high ovarian response group (oocyte retrieval ≥20, 842 cycles), the moderate ovarian response group (5< oocyte retrieval <20, 2008 cycles), and the low ovarian response group (oocyte retrieval ≤5, 991 cycles). The treatment outcomes were compared between the patients with an increased progesterone (P) level and the patients where the P level did not increase. With increase in ovarian response, the cut-off values of serum P on the day of human chorionic gonadotrophin (hCG) rose, and respectively were 2.5 ng/ml in the high ovarian response group, 2.25 ng/ml in the moderate ovarian response group, and 1.5 ng/ml in the low ovarian response group. In each group, the clinical pregnancy rate and embryo implantation rate were lower in the patients with an increased P level compared to those where the P level did not increase (all p < 0.05). However, there were no significant difference in the fertilization rate, cleavage rate, and high-quality embryo rate (all p > 0.05). The increased level of P on the day of hCG may affect the treatment outcomes of IVF-ET. The cut-off values of serum P seem to be associated with ovarian response. Increased ovarian response causes the cut-off values of serum P to rise.